2008
DOI: 10.1242/jeb.019901
|View full text |Cite
|
Sign up to set email alerts
|

Static electric field detection and behavioural avoidance in cockroaches

Abstract: SUMMARYElectric fields are pervasively present in the environment and occur both as a result of man-made activities and through natural occurrence. We have analysed the behaviour of cockroaches to static electric fields and determined the physiological mechanisms that underlie their behavioural responses. The behaviour of animals in response to electric fields was tested using a Y-choice chamber with an electric field generated in one arm of the chamber. Locomotory behaviour and avoidance were affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 49 publications
1
53
0
1
Order By: Relevance
“…This modelling provides accurate estimates of the magnitude of the electric fields within the Y-tube that can be correlated with the response of the flies at different field strengths [7]. In MAXWELL SV, the Y-tube was drawn as a simple two-dimensional x-y model with a cross-section taken from each part of the Y-tube (figure 1b).…”
Section: (A) Responses To Electric Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…This modelling provides accurate estimates of the magnitude of the electric fields within the Y-tube that can be correlated with the response of the flies at different field strengths [7]. In MAXWELL SV, the Y-tube was drawn as a simple two-dimensional x-y model with a cross-section taken from each part of the Y-tube (figure 1b).…”
Section: (A) Responses To Electric Fieldsmentioning
confidence: 99%
“…Thus, the surface area of the wings appears to be a major determinant of avoidance rather than the antennae or other structure such as the halteres. Previously, we suggested that electric fields could be detected via electrical forces causing deflection of sensory appendages resulting in mechanical stimulation [7]. Any electrically neutral object has a random distribution of negative and positive charges over the surface, and when that object enters an electric field it will experience forces on the electrons that cause an uneven distribution ( polarization) of charges.…”
Section: (B) Avoidance Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…several species of fish), may be evolutionary preserved in aquatic environments as it is an excellent conductor of EF, as well as in few terrestrial organisms (e.g. monotremes, Dictyostelium, cockroaches, bees and nematode worms) [2,[5][6][7][8][9][10]. The predominant use of electrosensation and movement at desired direction is utilized for identification of food such as prey and host, to escape from potential predator and navigation to different locations in an environment.…”
Section: Introductionmentioning
confidence: 99%
“…Deflection of hairs on the legs of spiders has also been reported when individuals are exposed to electric fields similar to those beneath power lines (Orlov and Romanenko, 1989). It has recently been shown that cockroaches are able to detect electric fields by means of their antennae (Hunt et al, 2005;Newland et al, 2008) and these movements underpin avoidance behaviour. The antennae are highly active and flexible appendages that are present on all insects (Okada and Toh, 2001;Schneider, 1964) and in cockroaches they contribute to escape responses via the activation of mechanoreceptors at the base of the antennae during movement Stierle et al, 1994).…”
Section: Introductionmentioning
confidence: 99%